2010
DOI: 10.1111/j.1469-8749.2009.03402.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic antiepileptic monotherapy, bone metabolism, and body composition in non‐institutionalized children

Abstract: AIM The aim of this study was to determine the influence of chronic monotherapy with antiepileptic drugs (AEDs) on vitamin D levels, bone metabolism, and body composition.METHOD Eighty-five children (38 males, 47 females; mean age 12y 5mo, SD 3y 4mo) were treated with valproate and 40 children (28 males, 12 females; mean age 11y 10mo, SD 3y) were treated with other AEDs (lamotrigine, sulthiame, or oxcarbazepine), comprising the non-valproate group. Forty-one healthy children (29 males 12 females; mean age 12y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 26 publications
4
48
3
Order By: Relevance
“…25,32,38 Several studies have shown that valproic acid was not associated with vitamin D deficiency. 36,38 Mean daily intake of vitamin D in our study was lower than that recommended by the Institute of Medicine (IOM). This might be due to subjects consuming only small amounts of milk and fish (sources of vitamin D), or sub-optimal vitamin D supplementation.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…25,32,38 Several studies have shown that valproic acid was not associated with vitamin D deficiency. 36,38 Mean daily intake of vitamin D in our study was lower than that recommended by the Institute of Medicine (IOM). This might be due to subjects consuming only small amounts of milk and fish (sources of vitamin D), or sub-optimal vitamin D supplementation.…”
Section: Discussioncontrasting
confidence: 69%
“…17,34,36,38,39 These latter studies found this to be the case for non-enzyme-inducing anticonvulsants (valproic acid) use 36,38 or new anticonvulsants (lamotrigine, topiramate, oxcarbazepine, sulthiamine). 17,39 In this study, none of the subjects had vitamin D deficiency, but we found higher prevalence of vitamin D insufficiency in epileptic children (39%) compared to control subjects (13%).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Older cytochrome P450-inducing AEDs such as phenytoin, phenobarbital and carbamazepine are associated with low bone mass and vitamin D deficiency resulting in increased fracture risk. However, the newer AEDs with minimum or no enzyme-inducing effects have demonstrated a better safety profile on bone metabolism (85). Immobility and neurological conditions that increase the risk of fall as well as co-morbidities limit the interpretation of human studies assessing the effect of AEDs on bone.…”
Section: Epilepsy and Antiepileptic Drug Therapymentioning
confidence: 99%
“…The initial search yielded 1603 research reports, of which 228 were excluded due to identical title or authors; 1056 were excluded due to ineligible study design (including non-human studies, review articles, case reports, comment, letter, experimental study, and/or fractureonly outcome). After full-text screening, 22 studies were included (Chung and Ahn, 1994;Baer et al, 1997;Akin et al, 1998;Kafali et al, 1999;Erbayat Altay et al, 2000;Verrotti et al, 2002;Voudris et al, 2002;Ecevit et al, 2004;Oner et al, 2004;Babayigit et al, 2006;Kumandas et al, 2006;Nicolaidou et al, 2006;El-Hajj Fuleihan et al, 2008;Nettekoven et al, 2008;Gniatkowska-Nowakowska, 2010;Rauchenzauner et al, 2010;Babacan et al, 2012;Dimić et al, 2013;Razazizan et al, 2013;Turan et al, 2014). Table 1 summarizes the characteristics of the included studies published between 1994 and 2014.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%